Development Of Subject Teacher Consultation Management In Improving The Competence Of The Qur’an Hadits’ Teachers In Madrasah Aliyah In Demak District - Zarkasi, Zarkasi (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
This research is a case study which takes a research in Islamic Senior high school at religion ministry in Demak district and D.I. Yogyakarta Province. While the data collection is done by documentary, observation, and deep interview with the head of Islamic education school section at religion ministry district office of D.I. Yogyakarta province and Demak District, the chief of management of teacher’s subject forum, Al-Qur’an Hadits’ teacher and the chief workgroup of madrasah. Data analysis is processed when the researcher were in field, collecting the data, and when all of data is collected as finishing of field section. The result of this research shows that : 1) teacher’s subject forum management in Islamic senior high school Demak District has some problems in main programe agenda, human resource, infrastructure and facilities, a management, a financial, controlling and evaluation. 2) Management development of teacher’s subject forum in D.I Yogyakarta province is covering the development of programs and agenda, human resource, infrastructure and facilities, a management, a financial, controlling and evaluation. 3) the lesson that can be learnt from both of research subject is do the system development correctly, program and structure to improving and developing the teacher’s subject forum management in Demak district to become professional organization that can improve the teacher’s competence.